National estimates of the use and outcomes of extracorporeal membrane oxygenation after acute trauma. Issue 1 (6th February 2019) - Hu, Parker J; Griswold, Lauren; Raff, Lauren; Rodriguez, Rachel; McGwin, Gerald; Kerby, Jeffrey David; Bosarge, Patrick
Abstract : Background: The use of extracorporeal membrane oxygenation (ECMO) as salvage therapy for patients with severe acute respiratory distress syndrome is gaining greater acceptance among trauma intensivists. The objective of this study was to review ECMO usage in trauma patients in the USA. Methods: The National Inpatient Sample (NIS) from years 2002 to 2012 was queried for patients aged 15 and older treated with ECMO who had one or more acute traumatic injuries as defined by the International Diagnostic Codes, Ninth Edition (ICD-9). The primary outcomes of interest were incidence of ECMO and overall inpatient mortality. Results: A total of 1347 patients were identified in the NIS database who had both ECMO performed and ICD-9 codes consistent with trauma. Patients were predominantly aged 15 to 29 years (31.4%) and were male (65.5%). The incidence of ECMO for patients after traumatic injuries has increased 66-fold during the 10-year period. In-hospital mortality was 48.0% overall, with a decreasing trend during the study period that approached statistical significance (p=0.06). Discussion: Although ECMO use in patients in the post-trauma setting remains controversial, there is an increasing trend to use ECMO nationwide, suggesting an increasing acceptance and/or increased availability at trauma centers. Given the decrease in mortality during the study period, ECMO as a salvage method in trauma patients remains a potentially viable option. Evaluation in a prospective manner may clarify risks and benefits. Level of evidence: Level IV, epidemiological.